Peningkatan Hasil Belajar Siswa Melalui Model Pembelajaran Problem Basic Learning Berbasis Higher Order Thinking Skills - Sitti Marlina; Sapinah Sapinah; Muh. Hadir Multi Partai (Lembaga Penelitian Mahasiswa Penalaran UNM, 2022)
This research is a classroom action research that uses a learning model of basic learning problems based on hinger order thinking skills to determine the effect on student learning outcomes in Class XI Economics at SMA Yaspib Bontolemngan. This type of research is an experimental research form of One Group Pretest Posttest Design. The research was carried out in the Odd Semester 2020/2021. The research subjects totaled 19 people. The research instruments used were tests, observations and documentation. The data analysis technique used was descriptive and inferential analysis and then analyzed using the t-test through the SPSS program which previously went through the normality and homogeneity test stages. Based on the hypothesis testing that has been done, it was found that student learning outcomes in Economics class XI SMA Yaspib Bontolemngan were influenced by the use of problem basic learning learning models based on hinger order thinking skills. This is proven after looking at the significance value of the data processing result tie which is 0.000 <0.05, which means that student learning outcomes in Economics Class XI SMA Yaspib are influenced by the use of a basic learning problem learning model based on hinger order thinking skills.